THE EFFECT OF URBAN EXPANSION ON RURAL HOUSEHOLD LIVELIHOOD AND THEIR COPING STRATEGIES IN THE CASE OF GUTO-GIDDA WOREDA, EAST WALLAGA ZONE OROMIA, ETHIOPIA - Gadisa Teshome Chali (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Urban expansion is a growing phenomenon in many developing countries, including Ethiopia. This study aims to investigate the effect of urban expansion on rural household livelihoods and their coping strategies in the case of Guto-Gidda Woreda, East Wallaga Zone, and Oromia, Ethiopia. The data were obtained from 129 randomly selected respondents by using questionnaires, focus group discussion and interview from Guto-Gidda Agricultural Office, Municipality Office Workers and other indigenous peoples of the study. Secondary sources were also used in the study. The collected data were edited, tabulated, has changed to percentage and finally descriptive method is employed. The result revealed that there are many factors causing urban expansion to rural household livelihood in the study area. These are like investment, infrastructure, rural to urban movement and positive consequences of urban expansion. Such as advance in communication, eclectic power, health and education facilities and also negative consequences of urban expansion such as loss of agricultural land, expansions of crimes, land degradation, family dispersion, housing problems. So that, displaced rural households have the likelihood of participating in non-agricultural livelihood strategies. Unlike to these factors, size of cropland, livestock asset, and credit were negatively and significantly correlated with participation in the non-agricultural livelihood strategies. Regardless of the diverse livelihood strategies practiced by displaced rural households, the propensity score matching estimation has indicated, fully displaced rural households received, on average, a per capita income of Birr 50,000 and Birr 30,000 for displaced rural household’s compensation respectively. This show regardless of compensations, fully displaced people have failed to establish a comparable means of income earnings and they are pursuing asset depleting consumption style. This shows for pre- displacement precautionary measures and post-displacement adaptation measures. And lastly the patterns of urban expansion are the major ones. To regulate the impact of urban expansion that found in the city the participation of government and dwellers of the displaced people in the city are very necessary.